Flavonoid and lignan intake in relation to bladder cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study - Zamora-Ros, R (Br J Cancer, 2014)
BACKGROUND: There is growing evidence of the protective role of dietary intake of flavonoids and lignans on cancer, but the association with bladder cancer has not been thoroughly investigated in epidemiological studies. We evaluated the association between dietary intakes of total and subclasses of flavonoids and lignans and risk of bladder cancer and its main morphological type, urothelial cell carcinoma (UCC), within the European Prospective Investigation into Cancer and Nutrition (EPIC) study. METHODS: A cohort of 477 312 men and women mostly aged 35–70 years, were recruited in 10 European countries. At baseline, dietary flavonoid and lignan intakes were estimated using centre-specific validated questionnaires and a food composition database based on the Phenol-Explorer, the UK Food Standards Agency and the US Department of Agriculture databases. RESULTS: During an average of 11 years of follow-up, 1575 new cases of primary bladder cancer were identified, of which 1425 were UCC (classified into aggressive (n=430) and non-aggressive (n=413) UCC). No association was found between total flavonoid intake and bladder cancer risk. Among flavonoid subclasses, significant inverse associations with bladder cancer risk were found for intakes of flavonol (hazard ratio comparing fifth with first quintile (HR(Q5–Q1)) 0.74, 95% confidence interval (CI): 0.61–0.91; P-trend=0.009) and lignans (HR(Q5–Q1) 0.78, 95% CI: 0.62–0.96; P-trend=0.046). Similar results were observed for overall UCC and aggressive UCC, but not for non-aggressive UCC. CONCLUSIONS: Our study suggests an inverse association between the dietary intakes of flavonols and lignans and risk of bladder cancer, particularly aggressive UCC.